Family Screening of Thalassemic Patients and Effectiveness of Education in Providing Knowledge about Prevention of Thalassemia - Rameez Iqbal, Sidrah, Asfahan Akhtar, Kiran Memon, Muhammad Rahil Khan, Muhammad Anique, Kiran Aamir, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To identify the carriers in the families of Beta Thalassemia patients and to determine the effectiveness of education about the prevention of thalassemia. Methods: The Observational - Cross-Sectional study was carried out in 6 months from 01-09-2021 to 31-03-2022 on a sample of 73 thalassemia patients and their families, after taking informed written consent. This study was conducted via non-probability, convenient sampling and was carried out at the Department of Pathology & Diagnostic and Research Laboratory - LUMHS Hyderabad/Jamshoro. The data was analyzed via SPSS 21.0 Results: The mean age of patients was found to be 17.34 + 7.32 years. 52% of participants were males with mean age of 15.23 + 9.67 years and 48% participants were females with mean age of 13.48 + 5.7 years. Most of the patients were having fortnightly blood transfusion i.e. 42.8% followed by 32.9% patients with monthly transfusion. Bi-monthly transfusion were found to be least reported. Consanguineous marriage among parents was found in 87.70% of patients. Hb electrophoresis pattern among siblings of thalassemia patients showed 4.1% occurrence of thalassemia major and 32.8% occurrence of thalassemia minor while 63% patients were found to be having normal electrophoresis pattern. The mean hemoglobin was found to be 09.23 + 3.65 mg/dl among siblings of thalassemia patients with 63.86 + 8.41 mg/dl mean MCV. Conclusion: The study found out that the around 2/3rd of the families were having positive history of thalassemia with around 1/4th of the patients had history of blood transfusion. The educational session was found to effective in improving the knowledge regarding the thalassemia. Keywords: Thalassemia, carriers, family history, effectiveness of educational awareness